HUBUNGAN DUKUNGAN EMOSIONAL TEMAN SEBAYA DENGAN SELF ADJUSTMENT PADA MAHASISWA RANTAU BIMBINGAN DAN KONSELING DI UNIVERSITAS JAMBI - Simanullang, Adelina Rodia; Sutja, Akmal; Fitriana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by overseas students facing adaptation challenges in new environments, including cultural, linguistic, and social differences, potentially causing stress, anxiety, and loneliness. Peer emotional support is an important factor that can assist overseas students in self-adjustment. This research aims to identify the level of peer emotional support, identify the level of self-adjustment, and examine the significant positive relationship between both variables among overseas students in the Guidance and Counseling Study Program at Universitas Jambi, class of 2025. This study uses a quantitative correlational method. The population was 113 overseas students, with a sample of 76 students determined by purposive sampling. The instrument was a Likert scale questionnaire tested for validity and reliability, with Cronbach's Alpha values of 0.917 for emotional support and 0.924 for self-adjustment. Data analysis included normality, linearity, Product Moment correlation, and hypothesis testing. The results showed: (1) peer emotional support was in the medium category (26.32%); (2) self-adjustment of overseas students was in the medium category (31.58%); (3) there is a significant positive relationship between peer emotional support and self-adjustment, evidenced by a significance value of 0.000 (p < 0.05) and a correlation coefficient of 0.610, indicating a medium relationship.